Compression injury of the suprascapular nerve - Ruiz-Cotorro, A.; Vilaro Angulo, J. (2001)
Introduction Compression injury of the suprascapular nerve is an uncommon injury that sometimes remains undiagnosed. However, this neuropathy has a florid clinical course and correct examination will reveal muscular hypotrophy with the accompanying pathological manifestations. The suprascapular nerve (C5-C6) stems from the superior primary trunk of the brachial plexus. After crossing the cervical muscle, it enters the supraspinatus fossa and passes through the coracoid notch (also known as the suprascapular notch) below the transverse scapular ligament (Figure 1). The suprascapular artery and vein pass above the transverse scapular ligament, lateral to the nerve. Where the two branches (C5 and C6) join, a motor branch to the supraspinatus muscle and sensory nerves for the acromio-clavicular and gleno-humeral joints split off. Further, distally in the course of the nerve, there is a motor branch to the infraspinatus muscle (Figure 2).